(untitled) (Південний архів (історичні науки), 2022)
Purpose is to investigate one of the little-known pages of the history of the Holocaust in Kherson on the basis of the investigation case of Yakov Wilhelmovich Ber-Bayer, this is stored in the state archives of the Kherson region. Research methods. During the research the method of archival heuristics was used, with the help of which the case was identified in the fund of the Security Service of Ukraine in Kherson region. To verify the information contained in the case, methods of source analysis were used: the circumstances of the investigation were studied, a comparative analysis of similar cases initiated by the Soviet security services during this period on similar charges, analyzed the structure of the case, to determine the completeness of documents. Following the principle of historicism, the context of the historical epoch is studied: the events that led to the accusation – the Holocaust during the Second World War in Ukraine, the causes, motives and consequences of state security bodies in relation to national minorities, in particular Germans. For this purpose, archival documents from the archival department of the SBU in the Kherson region, the state archives of the Kherson region, scientific literature, periodicals and eyewitness memoirs were involved. The results of the study: analysis of historiographical and source base showed that the events described in the case took place in Kherson in 1941, in their epicenter were Jews – patients of Kherson Infectious Diseases Hospital, arrested and shot by the Nazi occupation authorities. A study of similar practices in hospitals in occupied Ukraine suggests that hospital managements were involved in the Nazi identification of the Jewish population and in some cases directed the killing of their patients. The identification of the Jewish population in hospitals of all types on the basis of hospital cases of patients and the testimony of medical staff was undoubtedly carried out by the Nazis. Conclusions. As a result of the research, a new source on the history of the Holocaust was introduced into scientific circulation – the Ber-Bayer investigation case, which contains information about the murder of Jewish patients at the Kherson Infectious Diseases Hospital. Her study showed that the chief physician’s involvement in the deaths of his Jewish patients was not a central charge. Beer- Bayer was convicted as a German national – Volksdeutsche, but unlike many Germans rehabilitated in Soviet times, his conviction was not revoked due to collaborationism – he was rehabilitated only in 1993. A possible mitigating factor was that Ber-Bayer, later in Czechoslovakia, saved patients, in particular Jews, from persecution by the Gestapo.